Loose Coupling of Gis and Bim Data Models for Automated Compliance Checking Against Zoning Codes - Demir Altıntaş, Yelin; İlal, Mustafa Emre; İlal, Mustafa Emre (Elsevier, 2021)
Modeling urban data is crucial for supporting automated code checking processes. Ideally, digitally modelled building codes and urban data should be retrieved from municipalities, and the digital building model should be checked automatically based on the collected information. However, BIM tools do not contain and do not allow managing geographical information at a neighborhood scale. Current GIS applications also do not store all of the information required by building codes. Even if they did, interoperability between GIS and BIM environments are problematic. This paper describes the development of a zoning domain model for automated compliance checking of building projects. The proposed model is illustrated through a proof-of-concept GIS application, where geometric and semantic data are stored, queried and exported as a GML file. Use of this data model for automated code checking is an example for how GIS data can seamlessly complement BIM data making expansion of BIM schemas unnecessary.
Keywords: Automated compliance checking; BIM; Data coupling; GIS; Interoperability